2009
DOI: 10.1186/1758-2946-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted methods for molecular structure elucidation: realizing a spectroscopist's dream

Abstract: BackgroundThis article coincides with the 40 year anniversary of the first published works devoted to the creation of algorithms for computer-aided structure elucidation (CASE). The general principles on which CASE methods are based will be reviewed and the present state of the art in this field will be described using, as an example, the expert system Structure Elucidator.ResultsThe developers of CASE systems have been forced to overcome many obstacles hindering the development of a software application capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…Both structures are presented with the 13 C chemical shift assignment suggested by authors: [37] Steglich and Hellwig [38] have shown that structures 1 and 2 are wrong, and the following alternative structural formulae for these compounds, 3 and 4, were offered and proved: For Boletunone A, we have shown [19] that application of StrucEluc allowed reliable determination of the right structure 3 in 0.15 s. We also demonstrated how the problem of Boletunone B could be solved very quickly and correctly in a systematic way. Since the Boletunone B story was used by Bagno et al [20] for challenging DFT chemical shift calculations used as an analytical tool, we will explain here the solution of this problem in more detail.…”
Section: Example 1 Boletunones a And Bmentioning
confidence: 97%
See 2 more Smart Citations
“…Both structures are presented with the 13 C chemical shift assignment suggested by authors: [37] Steglich and Hellwig [38] have shown that structures 1 and 2 are wrong, and the following alternative structural formulae for these compounds, 3 and 4, were offered and proved: For Boletunone A, we have shown [19] that application of StrucEluc allowed reliable determination of the right structure 3 in 0.15 s. We also demonstrated how the problem of Boletunone B could be solved very quickly and correctly in a systematic way. Since the Boletunone B story was used by Bagno et al [20] for challenging DFT chemical shift calculations used as an analytical tool, we will explain here the solution of this problem in more detail.…”
Section: Example 1 Boletunones a And Bmentioning
confidence: 97%
“…Both algorithms are implemented in the CASE expert system Structure Elucidator, [16 -18] and their high speed and accuracy has strongly influenced the CASE strategy. [19] The third algorithm included into the set of system predictors is based on a fragment method. [1] Although this method is not as fast as the other two, it allows the user to obtain a detailed explanation as to how each predicted chemical shift was calculated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, it is very straightforward to scale up or fractionate LC-effluents to obtain larger quantities of purified metabolites for structure elucidation, for example by subsequent 2D-NMR analysis (Nakabayashi et al, 2009). Identification of NMR spectra has been greatly improved by the availability of public databases such as NMRshiftDB, MadisonMetabolome DB (Cui et al, 2008) and tools for automated elucidation of metabolites by machine-learned NMR prediction (Elyashberg et al, 2009). And last, a wider range of mass spectrometer types and ionization modes is in widespread use for LC-based separations compared to GC-options, from very sensitive QQQ machines for target quantification over ion traps and Qtraps to high-resolution mass spectrometers such as QTOFs, FT-ICR and Orbitrap instruments.…”
Section: Liquid Chromatography -Tandem Mass Spectrometrymentioning
confidence: 99%
“…For these applications, quantitative analysis has been conducted using various regression algorithms with standard gases or synthetic calibration spectra with absolute accuracies on 30 were reproduced, provided that relevant training samples were available in the library. Much of the work was motivated by pattern matching and classification of spectra for unknown samples (Robb and Munk, 1990;Novic and Zupan, 1995), and automated band assignment and identification of the underlying fragments typically performed by trained spectroscopists (Sasaki et al, 1968;Gribov and Elyashberg, 1970;Christie and Munk, 1988;Munk, 1998;Hemmer, 2007;Elyashberg et al, 2009). …”
mentioning
confidence: 99%